Comparative analysis of 15 chemical constituents in Scutellaria baicalensis stem‐leaf from different regions in China by ultra‐high performance liquid chromatography with triple quadrupole tandem mass spectrometry. Issue 18 (14th August 2017) - Yan, Baofei; Xu, Weijie; Su, Shulan; Zhu, Shaoqing; Zhu, Zhenhua; Zeng, Huiting; Zhao, Ming; Qian, Dawei; Duan, Jin‐ao
Abstract: Scutellaria baicalensis is a traditional Chinese herbal medicine containing multiple components, which has been extensively used in clinics to treat epidemic febrile disease and hyperactivity cough. To get a deeper understanding about Scutellaria baicalensis stem‐leaf resources, we analyzed 15 chemical constituents in 35 batches of Scutellaria baicalensis stem‐leaf from eight regions in China. A rapid, simple, and sensitive method using ultra‐high performance liquid chromatography coupled with triple quadrupole electrospray tandem mass spectrometry has been developed for the first time to simultaneously determine 15 chemical constituents (including phenolic acids and flavonoids) in Scutellaria baicalensis stem‐leaf. Sufficient separation of 15 target constituents was achieved on a Waters Acquity UPLC BEH C18 (2.1 mm × 100 mm, 1.7 μm) column within 14 min under the optimized chromatographic conditions. The established method was validated and showed good linearity, precision, repeatability, stability, and recovery and was successfully applied for the simultaneous determination of the 15 chemical constituents in these samples. Hierarchical clustering analysis and principal components analysis were performed to estimate and classify these samples based on the contents of the 15 chemical constituents. This study provided theoretical basis and scientific evidence for the development and utilization of Scutellaria baicalensis stem‐leaf resources.